If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1 = 5 + 6 Reorder the terms: -1 + x = 5 + 6 Combine like terms: 5 + 6 = 11 -1 + x = 11 Solving -1 + x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 11 + 1 Combine like terms: -1 + 1 = 0 0 + x = 11 + 1 x = 11 + 1 Combine like terms: 11 + 1 = 12 x = 12 Simplifying x = 12
| 6-x=2*3 | | 6-x=2.3 | | (a/b)2 | | 5x-3(2x-4)=3(4x-1)+5/2 | | -4x-1=-2x+7 | | x+10-5=20-5+6x | | x+10-5=20-5 | | 2x^2-28x-2+c=-50 | | 11x-121=5x-7 | | 7p^2+10p+3=0 | | 182-5x=31x+22 | | t(2y+4p)+(n+3h)=24 | | 9+4+7=29 | | m^4-2m^3+2m-1=0 | | t^3-500t-3750=0 | | 2(x+16)+4(67x-6)=0 | | 57-6x=21x+15 | | -y=-3x+(-14) | | 2x-3=5-2 | | 1y=1x-1 | | 2(2x-5)=11 | | 35x=-35 | | 4+3x-2=7x+8-3 | | 25x^2+5*x-12= | | 25x^2+5*x-12=0 | | 6x^2+4x+5=0 | | 1y=1x+16 | | 3*10-5*10-1=19 | | 7(2x+2y)=-14(-35) | | 3x-5x-1=19 | | x+0.07X=200 | | 4x^2-11x+27=6x+9 |